DETECTION OF FRAUDULENT FINANCIAL STATEMENT THROUGH PENTAGON THEORY WITH AUDIT COMMITTEE AS MODERATING - Indriyani, Ely; Suryandari, Dhini (EAJ (Economic and Accounting Journal), 2021)
This study aims to examine financial targets, financial stability, external pressure, personal financial needs, effective monitoring, nature of industry, total accruals, change of directors, and CEO duality in detecting fraudulent financial statements with the audit committee as the moderating variable. The population of this research is 20 state-owned companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. Sampling using saturated sampling technique and obtained a final sample of 100 units of analysis. Data collection using documentation techniques. The data analysis technique used regression analysis and Moderated Regression Analysis (MRA). The results of this study indicate that external pressure and the nature of industry have a significant positive effect on the detection of fraudulent financial statements. The audit committee is able to moderate the influence of financial targets, external pressure, nature of industry, and change of directors on the detection of fraudulent financial statements